Knowledge, attitudes, and experiences of a group of turkish dentists regarding child abuse = Conocimientos, actitudes y experiencias de un grupo de dentistas turcos en relación con el abuso infantil - Ceyhan, Derya
Child abuse is a universal problem with critical lifelong effects. This study aimed to evaluate knowledge, attitudes, experiences of dentists regarding child abuse and to increase relevant awareness of them. A self-administered questionnaire with 48 questions about dentists' personal and educational information and their level of knowledge, attitudes, experiences on child abuse was implemented. Out of targeted 305 participants, 183 (60.0%) returned completely filled out questionnaires. Majority of participants knew signs and symptoms of child abuse. Of the participants, more than half were well-informed on what to do, however, one quarter had no knowledge about where to report in case of child abuse. In identifying child abuse, 39.3% of the participants found themselves inadequate. The most commonly stated reason for low rate of reporting was hesitancy to identify the case as abuse, and all participants needed more training. Only 12 (6.6%) participants suspected a case of child abuse. Dentists who had children and were long-time experienced and generalist did not have sufficient knowledge about legal obligations, signs and symptoms of child abuse (p<0.05). Arrangements and training programs to increase knowledge, awareness, and responsibility levels of dentists about child abuse appear to be a critically important topic.